Comparative Study of Sports Participation Index in Wonogiri Regency in 2017 and 2020 - Salma Faizatunnikmah; Djoko Nugroho; Waluyo Waluyo (PHEDHERAL, 2020)
This research uses descriptive and comparative research methods. The sampling technique in this study was stratified random sampling with cluster sampling. The samples taken in this study were Wonogiri District as a district with high population density, Slogohimo sub-district as a district with medium population density and Pracimantoro District as a sub-district with low population density and divided into age group and gender, totaling 270 people. The data collection technique in this study was a questionnaire technique. The reliability test in this study is guided by the SDI instrument as an instrument for measuring the results of sports development which has been trusted because it has been patented in the book Sport Development Index 2007 by Cholik and Maksum. The validity test of the measuring instrument used is the standard set in the Sport Development Index (SDI). The data analysis technique in this research is the stage of data collection, data reduction, data presentation, and drawing conclusions. The results of this study are: (1) the sports participation index in Wonogiri Regency is 0.388. The index was obtained by combining the sports participation index in Wonogiri District of 0.588, the sports participation index in Slogohimo District of 0.488, and the participation index of the Pracimantoro District of 0.477. The sports participation index of Wonogiri Regency shows that the level of sports participation is included in the low category, (2) The comparison of sports participation in Wonogiri Regency in 2017 and 2020 is sports participation in 2017 of 0.237 while sports participation in 2020 is 0.388 which means sports participation in Wonogiri Regency 2020 has increased and is better than in 2017, (3) The sports development of Wonogiri Regency in terms of sports participation is still far from being good or advanced, there are many things that need to be considered and addressed by the Wonogiri Regency government.